What could be the function of f ( x ) be if this differential equation is satisfied?
2 f ′ ( x ) + f ′ ( 2 x ) + 4 f ( 2 x ) − 3 = f ( x ) ( ( f ′ ( x ) + f ( x ) )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
One can first note that expressions for f ( x ) with ln ( g ( x ) ) will have a term of order O ( ln 2 ( g ( x ) ) ) that doesn't cancel out.
Letting f ( x ) = A e B x + C , the LHS becomes: 2 A B e B x + A B e 2 B x + ( 4 A e 2 B x + 4 C ) − 3 = A ( B + 4 ) e 2 B x + 2 A B e B x + ( 4 C − 3 ) .
RHS becomes: ( A e B x + C ) ( A B e B x + ( A e B x + C ) ) = A 2 ( B + 1 ) e 2 B x + A C ( B + 2 ) e B x + C 2
Equating terms of same order:
O ( 1 ) : C 2 = 4 C − 3 ⇒ C = 1 or 3 .
O ( e B x ) : 2 A B = A C ( B + 2 ) ⇒ B = 2 − C 2 C = 2 or − 6 for respective values of C.
O ( e 2 B x ) : A ( B + 4 ) = A 2 ( B + 1 ) ⇒ A = B + 1 ( B + 4 ) = 2 or 5 2 .
Hence solutions in this form are: 2 e 2 x + 1 or 5 2 e − 6 x + 3 .
I did it similarly, but are there any other solutions??? Solutions which are not necessarily in this form..........How do we go about finding them???
I mean f ( x ) = 1 and 3 are solutions on their own.
@Alex Burgess Haha.. I didn't even notice the constant functions as solutions! Nice observation..
Ok, so one could consider a general Taylor series: f ( x ) = ∑ n = 0 ∞ a n x n .
Then, looking at the orders of O ( x n ) in the equation, we get:
( n + 1 ) ( 2 + 2 n ) a n + 1 + 2 n + 2 a n − ∑ i = 0 n a i ( a n − i + ( n + 1 − i ) a n + 1 − i ) − 3 δ n , 0 = 0
Then you can factor out a n + 1 : a n + 1 ( n + 1 ) ( 2 + 2 n − a 0 ) = g ( a 0 , a 1 , . . . a n ) for some function g .
Hence the terms a n will be finite if a 0 = ( 2 + 2 n ) ∀ n ∈ N .
For large n : a n + 1 ( n + 1 ) ( 2 n ) ≈ − 2 n + 2 a n , so a n + 1 ≈ − n + 1 4 a 0 , and by the alternating series test, this converges.
For a 0 = 3 , we get ( 0 ) a 1 = ( 0 ) , so a 1 could take any value.
For a 0 = 1 , we get a n = 0 ∀ n ∈ N .
Log in to reply
This is beautiful. Just if we assume that the solution is an analytic function.
By f'(2x) should we not mean d/dx(f(2x))?
Nice guess. But if we want to find all possible solutions it is a headache. May be we can use existence uniqueness theorem or some other technique.
Problem Loading...
Note Loading...
Set Loading...
Evaluated the given equation at 0 :
3 f ′ ( 0 ) + 4 f ( 0 ) = f ( 0 ) f ′ ( 0 ) + f ( 0 ) 2 + 3 .
Wasn't hard to find out the answer after this.
Again, it doesn't help arrive at the solution..